Congruent action context releases Mu rhythm desynchronization when visual objects activate competing action representations. (April 2023) - Wamain, Yannick; Godard, Marc; Puffet, Anne-Sophie; Delepoulle, Samuel; Kalénine, Solène
Abstract: Recent findings demonstrated that object perception is affected by the competition between action representations. Simultaneous activation of distinct structural ("grasp-to-move") and functional ("grasp-to-use") action representations slows down perceptual judgements on objects. At the brain level, competition reduces motor resonance effects during manipulable object perception, reflected by an extinction of μ rhythm desynchronization. However, how this competition is solved in the absence of object-directed action remains unclear. The present study investigates the role of context in the resolution of the competition between conflicting action representations during mere object perception. To this aim, thirty-eight volunteers were instructed to perform a reachability judgment task on 3D objects presented at different distances in a virtual environment. Objects were conflictual objects associated with distinct structural and functional action representations. Verbs were used to provide a neutral or congruent action context prior or after object presentation. Neurophysiological correlates of the competition between action representation were recorded using EEG. The main result showed a release of μ rhythm desynchronization when reachable conflictual objects were presented with a congruent action context. Context influenced μ rhythm desynchronization when the action context was provided prior or after object presentation in a time-window compatible with object-context integration (around 1000 ms after the presentation of the first stimulus). These findings revealed that action context biases competition between co-activated action representations during mere object perception and demonstrated that μ rhythm desynchronization may be an index of activation but also competition between action representations in perception.